2018
DOI: 10.1109/mcomstd.2018.1700057
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Fog Computing for Industrial Automation Through Time-Sensitive Networking (TSN)

Abstract: In this article, we advocate for the use of IEEE 802.1 Time-Sensitive Networking (TSN) as deterministic transport for the network layer of fog computing in industrial automation. We give an overview of the relevant TSN protocol services and motivate the use of TSN. We propose a configuration agent architecture based on IEEE 802.1Qcc and OPC Unified Architecture (OPC UA), capable of performing runtime network configuration. We briefly present the configuration challenges for scheduled networks (considering a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 9 publications
0
59
0
Order By: Relevance
“…Further related work that is complementary to our study has been conducted by Pop et al [11], Hackel et al [12], Herlich et al [13], Nayak et al [14]- [16], and Kobzan et al [17].…”
Section: B Related Workmentioning
confidence: 54%
“…Further related work that is complementary to our study has been conducted by Pop et al [11], Hackel et al [12], Herlich et al [13], Nayak et al [14]- [16], and Kobzan et al [17].…”
Section: B Related Workmentioning
confidence: 54%
“…To make MEC an enabler for latency-critical IIoT applications, time-sensitive networking (TSN) 2 is a vital solution. [193] proposed TSN-based configuration architectures of MEC that can support real-time IIoT applications. Considering system resources, [155] reported that enabling MEC in IIoT systems can improve the system efficiency by jointly designing resource allocation and offloading based on an auction-based method where both claimed bids and asked prices were given by the MEC servers.…”
Section: ) Industrial Internetmentioning
confidence: 99%
“…The work in [27] presents a heuristic incremental scheduling algorithm to minimize the impact of reconfiguring schedules on existing flows. The work in [28] proposes a configuration agent architecture and a simple scheduling heuristic such that the schedules of dynamic flows can be quickly generated and configured. However, these algorithms do not consider the capacity limitation of network switches.…”
Section: Related Workmentioning
confidence: 99%